ERK1 regulates the hematopoietic stem cell niches. - Nathalie Saulnier; Soizic Guihard; Xavier Holy; Elodie Decembre; Pierre Jurdic; Denis Clay; Vincent Feuillet; Gilles Pagès; Jacques Pouysségur; Françoise Porteu; Murielle Gaudry (PLoS ONE, 2012)
The mitogen-activated protein kinases (MAPK) ERK1 and ERK2 are among the major signal transduction molecules but little is known about their specific functions in vivo. ERK activity is provided by two isoforms, ERK1 and ERK2, which are ubiquitously expressed and share activators and substrates. However, there are not in vivo studies which have reported a role for ERK1 or ERK2 in HSCs and the bone marrow microenvironment. The present study shows that the ERK1-deficient mice present a mild osteopetrosis phenotype. The lodging and the homing abilities of the ERK1(-/-) HSC are impaired, suggesting that the ERK1(-/-)-defective environment may affect the engrafment of HSCs. Serial transplantations demonstrate that ERK1 is involved in the maintenance of an appropriate medullar microenvironment, but that the intrinsic properties of HSCs are not altered by the ERK1(-/-) defective microenvironment. Deletion of ERK1 impaired in vitro and in vivo osteoclastogenesis while osteoblasts were unaffected. As osteoclasts derive from precursors of the monocyte/macrophage lineage, investigation of the monocytic compartment was performed. In vivo analysis of the myeloid lineage progenitors revealed that the frequency of CMPs increased by approximately 1.3-fold, while the frequency of GMPs significantly decreased by almost 2-fold, compared with the respective WT compartments. The overall mononuclear-phagocyte lineage development was compromised in these mice due to a reduced expression of the M-CSF receptor on myeloid progenitors. These results show that the cellular targets of ERK1 are M-CSFR-responsive cells, upstream to osteoclasts. While ERK1 is well known to be activated by M-CSF, the present results are the first to point out an ERK1-dependent M-CSFR regulation on hematopoietic progenitors. This study reinforces the hypothesis of an active cross-talk between HSCs, their progeny and bone cells in the maintenance of the homeostasis of these compartments.